Investigating Teachers’ and Students’ Evaluation of the Textbook English for Iraq for First and Second Grades of High School Based on Litz’s Checklist - Nafashi, Nada; Dabaghi, Azizollah; Ketabi, Saeed (Al-Adab Journal, 2024)
The present study investigates Iraqi teachers’ and students’ evaluation of the textbook English for Iraq for first and second grades of high school based on Litz’s checklist using a descriptive qualitative method. The sample of this study was 2textbook books entitled “English for Iraq for 1st Intermediate” and “English for Iraq for 2nd Intermediate”. The research data was collected from the Evaluation checklist of experts consisting of 5 Points in evaluation textbooks. The results of the evaluation of the two books have mostly met the standards of a decent book based on the criteria of Litz in terms of objectives, layout&design, methodology, skills, elements of language. This study also intended to examine EFL teachers’ and students’ points of view on these two textbooks. The participants were 70 first and second-grade intermediate school students and 30 EFL teachers who chose from various intermediate schools in Wasit province. The researcher designed two questionnaires to evaluate these textbooks. The examinations uncovered that EFL teachers were to some extent happy with the “English for Iraq textbook series”; Not with standing, EFL students were fairly impartial. The evaluation also indicated that the English for Iraq textbook meets the CLT educational plan’s points and targets in introducing the exercises and activities through legitimate texts (fiction and nonfiction) that are connected with genuine circumstances. The findings of this work may hold any importance with Iraqi EFL teachers, materials designers, and the partners engaged with the materials readiness Departments of the Iraqi Ministry of General Education.